2008
DOI: 10.1007/bf02982628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of malnutrition with the Mini Nutritional Assessment (MNA) in a nationally representative sample of elderly Taiwanese

Abstract: To the best of our knowledge, this is the first study to apply the MNA to estimate the prevalence of malnutrition in the elderly in a nationally representative sample. Results suggest that the MNA can identify malnourished elderly in a non-Caucasian population. However, it appears that the functionality of the instrument can be improved by adapting population-specific anthropometric cutoff standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
4
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 11 publications
3
39
4
1
Order By: Relevance
“…14 . However, they differ from those of other international studies conducted in a community in which the prevalence of undernutrition is lower and ranges between 1.7% and 5.8%, and undernutrition risk varies between 13.1% and 31.9% 12,[26][27][28][29] . The results obtained in the present study show the impact of this problem in Portugal and the need for immediate implementation of preventive and therapeutic measures.…”
Section: Discussionmentioning
confidence: 63%
“…14 . However, they differ from those of other international studies conducted in a community in which the prevalence of undernutrition is lower and ranges between 1.7% and 5.8%, and undernutrition risk varies between 13.1% and 31.9% 12,[26][27][28][29] . The results obtained in the present study show the impact of this problem in Portugal and the need for immediate implementation of preventive and therapeutic measures.…”
Section: Discussionmentioning
confidence: 63%
“…In comparison to community-dwelling elderly, several studies reported a high prevalence of malnutrition among elderly residing in NHs [3,12,13]. In Lebanon, the prevalence of both malnutrition and at risk of malnutrition among rural free elders living in their natural homes was 8% and 29.1% respectively [7].…”
Section: Discussionmentioning
confidence: 99%
“…Differences between institutionalized and non-institutionalized elderly have also been reported. The findings generally showed that all elderly living in institutions [3,12,13], and women in particular [4], tended to suffer from high prevalence of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status was measured using the 18-item Chinese version of the Mini-Nutritional Assessment (MNA; Guigoz, Vellas, & Garry, 1996;Tsai, Ho, & Chang, 2008). Summed scores less than 17.5 categorize older patients as malnourished with satisfactory reliability and validity reported for older Taiwanese (Tsai et al, 2008). The Cronbach's !…”
Section: Data Collection and Measuresmentioning
confidence: 99%